Race and Region: Tracing the Cultural Pathways of Rice Consumption in the United States, 1680-1960. Issue 3 (2nd September 2019) - Miller, Bonnie M.
ABSTRACT: This brief history of U.S. rice consumption from 1680 to 1960 traces the influences of race and region in shaping the prevalence of rice in certain communities over others. It examines the earliest cuisines that significantly integrated rice into the diet, in the Carolina Lowcountry and Cajun Louisiana during the colonial era and in the annexed Mexican territories of the Southwest and Asian communities of the West Coast in the nineteenth century. Outside those areas, rice was not generally consumed as a regular staple. As rice production expanded westward in the late nineteenth century, consumers in the newer areas did not embrace rice as the industry had expected. The turning point came after World War II when cooperative rice associations put forth national publicity campaigns to re-brand rice into a more cosmopolitan food commodity. This essay explores the factors that shaped when and how rice became a dietary staple for Americans across race and region.